PENGARUH LOCUS OF CONTROL DAN REGULASI DIRI TERHADAP MORAL DISENGAGEMENT PADA MAHASISWA TINGKAT PERTAMA DI UNIVERSITAS Al AZHAR INDONESIA - Rahmawati, Siti; Nurfadilah; Hadiansyah, Andri; Rosyid, Abdul; Junaedi Airadhika, Nawzha (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the influence of locus of control and self-regulation on moral disengagement in first-year students at Al-Azhar Indonesia University (UAI). Moral disengagement is a psychological mechanism that allows individuals to abdicate moral responsibility for harmful actions. This study used a quantitative approach with a correlational design and purposive sampling. The instrument consisted of valid and reliable locus of control, self-regulation, and moral disengagement scales. Multiple linear regression analysis showed that locus of control and self-regulation simultaneously had a significant effect on moral disengagement. However, partially, only self-regulation had a significant negative effect, while locus of control had no significant effect. The findings indicate that self-regulation is the dominant factor in suppressing moral disengagement in first-year students. Theoretical and practical implications are discussed for the development of psychologically based interventions in higher education.